Environmental Kuznets curves: Empirical relationships between environmental quality and economic development - Jon Strand (University of Oslo, Department of Economics, 2002)
This lecture discusses relationships between environmental and resource qualities and loads, and economic development, theoretically and empirically. We start in section 2 with a list of theoretical arguments that may or may not justify a tendency for environmental quality to first deteriorate, and subsequently improve, as per-capita incomes grow. In section 3 we go on to consider the empirical evidence on these issues, related to the concept of “environmental Kuzents curves” (EKC). This evidence indicates that estimated EKC relationships appear to largely hold for local pollution indicies, but less so for environmental and resource variables where effects occur on a global scale, such as biodiversity and carbon emissions. We discuss reasons for these differences, and their possible long-run implications.
Keywords: Q32; 330; economic development; resource loads; Wirtschaftswachstum; Umwelt; Theorie; Environmental Kuznets Curve